Study of Automatic Balancing for Flywheel-based Kinetic Energy Recovery System (KERS) - Ismail, Mohd Fareid Fareez (IRC, 2016)
Mass unbalance results from the lack of alignment between the geometric axis and the principal axis of inertia during manufacturing, and results in an unbalance force synchronous with rotor angular speed. The same problem happens in flywheel-based Kinetic Energy Recovery System (KERS). The purpose of this research is to introduce a new automatic balancing method which has the ability to effectively lessen radial vibration due to mass unbalance in vehicular flywheel-based KERS. The performance of this method has not been investigated on flywheel based-KERS before but it has been studied and implemented on washing machines, hand held grinder tools, CD-ROMs and optical disk drives. One issue that prohibits the implementation of flywheel-based KERS in road vehicles is the manufacturing cost of near-zero mass unbalance in composite material of the rim.